2020
DOI: 10.1038/s41467-019-13791-1
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast transient liquid assisted growth of high current density superconducting films

Abstract: The achievement of high growth rates in YBa 2 Cu 3 O 7 epitaxial high-temperature superconducting films has become strategic to enable high-throughput manufacturing of long length coated conductors for energy and large magnet applications. We report on a transient liquid assisted growth process capable of achieving ultrafast growth rates (100 nm s −1) and high critical current densities (5 MA cm −2 at 77 K). This is based on the kinetic preference of Ba-Cu-O to form transient liquids prior to crystalline therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
81
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(86 citation statements)
references
References 43 publications
4
81
1
Order By: Relevance
“…The present work conducted by our group showed the possibility to combine BaZrO 3 and BaHfO 3 NCs with YBa 2 Cu 3 O 7 (YBCO) type II superconductors, to enhance the superconducting properties, unravelling a novel pathway in electronic materials science and bestowing a crucial breakthrough for the implementation of NCs to act as pinning centres. [30][31][32] Thus, we present here a novel hybrid method (i.e., built from the classical approaches) to produce high-quality perovskite NCs and enhance the current applicability portfolio.…”
Section: Introductionmentioning
confidence: 99%
“…The present work conducted by our group showed the possibility to combine BaZrO 3 and BaHfO 3 NCs with YBa 2 Cu 3 O 7 (YBCO) type II superconductors, to enhance the superconducting properties, unravelling a novel pathway in electronic materials science and bestowing a crucial breakthrough for the implementation of NCs to act as pinning centres. [30][31][32] Thus, we present here a novel hybrid method (i.e., built from the classical approaches) to produce high-quality perovskite NCs and enhance the current applicability portfolio.…”
Section: Introductionmentioning
confidence: 99%
“…However, from the EGA-MS analysis in Fig. 5, only a low-temperature stage is observed: the most intense peak, at 200°C, still shows evolution of propionic acid (m/z=45, 29,28,27) corresponding to CuProp 2 decomposition, but an excess of m/z=28 (CO, N 2 or C 2 H 4 ) with respect to the case without TEA is detected. This might be an indication that a TEA effect is present up to 200°C, and thus that also its evaporation is reduced when CuProp 2 is added, due to the coordination between TEA and Cu 2+ of the carboxylic salt.…”
Section: Decomposition In Inert Atmospherementioning
confidence: 95%
“…In this work, we will apply thermal analysis (TA) on film samples, despite the limitation of the small sample amount in films which pushes TA techniques to their limits. We will provide a closer look on the pyrolysis of FF-YBa 2 Cu 3 O 7-∂ (YBCO) films [27][28][29], a high temperature superconductor (HTS) [30,31], by studying in-situ the effect of TEA on each of the three metalorganic salts used for the fabrication of YBCO with chemical methods: YProp 3 [22,24,32,33], CuProp 2 [20,[34][35][36], Ba-Prop-Ac [18]. Humid O 2 atmospheres will be studied in comparison to inert atmospheres, as the former are normally used during YBCO pyrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…However, fluorine-free precursor solutions method has a major drawback. The formation of BaCO 3 phases during the heat treatment can degrade the superconductivity of the YBCO films [15]. Several authors [16,17] reported on the successful decomposition during the heat treatment and obtained YBCO films with high critical current.…”
Section: Introductionmentioning
confidence: 99%